HUBUNGAN KOMUNIKASI PERAWAT DENGAN TINGKAT KECEMASAN KELUARGA PADA PASIEN TYPHOID YANG DIRAWAT DI PUSKESMAS SIBULUE KECAMATAN SIBULUE - Irawati; Arni AR; Nirmawati Darwis (Jurnal Ilmiah Mappadising, 2020)
In the implementation of the nursing process, it is never separated from the interaction process that occurs between nurses and patients and patients' families so that nurses must realize that communicating in health services is very influential or helps patients in the healing process and helps the patient's family so that the level of anxiety experienced is not excessive. The purpose of this study was to determine the relationship between nurse communication and family anxiety levels in typhoid patients who were treated at the Sibulue Health Center, Sibulue District, Bone Regency. The design used in this study was cross sectional. The sampling method used was total sampling with a sample size of 30 respondents. The research instrument used was a questionnaire and the data were analyzed using the SPSS 21 program. Bivariate analysis obtained Asymp sing (2-sided) in = 0.001 <α = 0.05. So it can be concluded that there is a relationship between nurse communication and anxiety levels in the patient's family typhoid being treated at the Sibulue Health Center, Sibulue District, Bone Regency in 2019. The suggestion for nurses at the Sibulue Health Center, Sibulue District, Bone Regency, is to improve their communication with the patient's family, especially those with typhoid so that the patient's family does not feel excessive anxiety. Abstrak Dalam pelaksanaan proses keperawatan tak pernah lepas dari proses interaksi yang terjadi antara perawat dengan pasien maupun keluarga pasien sehingga perawat harus menyadari bahwa berkomunikasi dalam pelayanan kesehatan sangat berpengaruh atau membantu pasien dalam proses penyembuhan dan membantu keluarga pasien agar tingkat kecemasan yang dialami tidak berlebihan. Tujuan penelitian ini adalah untuk mengetahui hubungan komunikasi perawat dengan tingkat kecemasan keluarga pada pasien typhoid yang dirawat di Puskesmas Sibulue Kecamatan Sibulue Kabupaten Bone. Desain yang digunakan dalam penelitian ini adalah cross sectional. Cara penarikan sampel dengan menggunakan total sampling dengan jumlah sampel sebanyak 30 responden. Adapun instrumen penelitian yang digunakan adalah kuesioner dan data dianalisis menggunakan program SPSS 21. Analisis bivariat diperoleh Asymp sing (2-sided) dalam =0,001< =0,05.Sehingga dapat disimpulkan bahwa ada hubungan antara komunikasi perawat dengan tingkat kecemasan pada keluarga pasien typhoidyang dirawat di Puskesmas Sibulue Kecamatan Sibulue Kabupaten Bone tahun 2019. Adapun saran untuk perawat Puskesmas Sibulue Kecamatan Sibulue Kabupaten Bone agar meningkatkan komunikasinya pada keluarga pasien khususnya penderita typhoidsehingga keluarga pasien tidak merasakan cemas berlebihan.